2018
DOI: 10.21037/jtd.2018.04.161
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous pleural drainage in patients taking clopidogrel: real danger or phantom fear?

Abstract: Despite being categorized as a procedure associated with a low risk of iatrogenic hemorrhage, percutaneous pleural drainage in patients taking the ubiquitous antiplatelet agent clopidogrel is still commonly perceived as a risky proposition. There is mounting evidence, however, in support of the safety of percutaneous needle procedures in persons receiving this medication. Establishing that these pleural interventions can be performed safely without clopidogrel interruption would be of great clinical significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The latest published review article summarizing the available data on this topic concluded that it might be safe to do urgent thoracocentesis on patients using clopidogrel. However, clopidogrel is better withheld for at least five days before the procedure when possible [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest published review article summarizing the available data on this topic concluded that it might be safe to do urgent thoracocentesis on patients using clopidogrel. However, clopidogrel is better withheld for at least five days before the procedure when possible [6].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies published recently found a significant risk of bleeding from performing these procedures on such patients. Thus, they recommended holding antiplatelet therapy, when possible, five days before such procedures or conducting large randomized controlled trials (RCTs) to assess its safety [6][7]. The Society of Interventional Radiology (SIR) published guidelines in 2012 which stated that for Category 1 procedures, including thoracocentesis, clopidogrel should be held for one to five days prior to 1 2…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that there is an acceptable safety profile to perform urgent thoracentesis or chest tube placement in patients taking clopidogrel, but that additional studies are needed. 15…”
Section: Risk Of Bleeding Due To Thoracentesismentioning
confidence: 99%